Learning to learn at the University: A marketing experience using the TAM - González-Gascón, Elena (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Learning to learn (LtL) competence is key to success in today’s society. A student with the LtL competence is one who promotes their self-learning. The Technology Acceptance Model (TAM) is used to understand the decision to adopt a new technology that accompanies a methodological change. The aim is to find out whether university students adopt self-learning as a learning strategy and if the TAM is valid when considering the LtL competence. The results indicate that methodologies should be designed to promote LtL among students, that the TAM is valid for LtL and, that the enjoyment construct is particularly relevant.